REFLECTIONS ON BRAZIL AND DEFENSE COOPERATION: BETWEEN HISTORIAL ADVANTAGES AND CHALLENGES (1822-PRESENT) - Rizzi, Kamilla Raquel; Jacon Ayres Pinto, Danielle (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2025)
<pre id="tw-target-text" class="tw-data-text tw-text-large tw-ta" dir="ltr" data-placeholder="Tradução" data-ved="2ahUKEwjutpznrc-IAxVIjZUCHQNkMgMQ3ewLegQICBAU" aria-label="Translated text: This is research that analyzes defense cooperation in Brazil, seeking to facilitate a theoretical discussion and a proposal for the historical periodization of defense cooperation actions in Brazil. When answering what are the most evident characteristics of cooperation in Brazil's defense, as a working hypothesis it is pointed out that there are a) advantages and challenges in Brazil's defense cooperation actions, b) a correlation between foreign policy and defense in these actions and c) the mapping of priority areas is evident. Defense cooperation is a strategy that involves collaboration between countries to increase defense capabilities, share information, conduct joint training, develop technologies and strengthen diplomatic ties. The literature review in the theoretical area points to several possibilities, understandings and paths for defense cooperation, but in this research we opted to use the concept of stability as a factor that generates cooperation, as well as the evolution of the correlation between foreign and defense policy. in Brazilian history.">This research analyzes Defense cooperation in Brazil, seeking to facilitate a theoretical discussion and a proposal for a historical periodization of the actions of this type of cooperation in Brazil. When answering which are the most evident characteristics of cooperation in the area, as a working hypothesis it is pointed out that there are a) advantages and challenges in the actions of Defense cooperation in Brazil, b) a correlation between Defense and foreign policy in these actions and c) the mapping of priority areas throughout history is evident. Defense cooperation is a strategy that involves collaboration between countries to increase defense capacity, share information, conduct joint training, develop technologies and strengthen diplomatic ties. The review of the theoretical literature in the area points to several possibilities, understandings and paths for Defense cooperation, but in this research it was chosen to use the concept of stability as a factor generating cooperation, as well as the evolution of the correlation between Defense and foreign policy in Brazilian history.